Hypocrisy is the tribute that vice pays to virtue: Dynamics of perceived organization hypocrisy and job embeddedness in the hospitality industry - Zeb, Faheem; Wang, Qingjin; Shahjehan, Asad (Frontiers in Psychology, 2023)
In the wake of the COVID-19 pandemic hospitality institutions are striving for legitimacy, which leads them to organizational hypocrisy, generating perceptions of inducement breach, future anxiety, and ultimately reduced Job Embeddedness. This study has identified industry and environmental situation-specific constructs in a mutual relationship to fill a theoretical gap. An electronic survey of 2100 frontline employees was administered among which 842 completed surveys were retained for analysis. The validity of the measures and the absence of common method bias were established. SPSS PROCESS was used to compute the serial mediation effects. Contrary to existing knowledge, the results of this study indicate that organizational hypocrisy increases employee job embeddedness. Three reasons identified for this result are Asian culture sample, prevalence of COVID-19 pandemic, and the necessity of hypocrisy emphasized by scholars. The study also presents an underlying mechanism that makes this relationship negative through perceived inducement breach and future anxiety. This study focuses on HOW and IF organizational hypocrisy has detrimental effects, thus adding empirical evidence to otherwise exploratory literature. For hospitality industry employees are an irreplaceable resource that provides competitive advantages, they need to align their values with that of their employees by word and actions or risk losing them.